The significance of batch and patch test method in establishing contact allergy to fragrance mix I: EDEN Fragrance Study Group - Bruze, Magnus; Mowitz, Martin; Ofenloch, Robert; Coenraads, Pieter-Jan; Diepgen, Thomas L.; Elsner, Peter; Gonçalo, Margarida; Naldi, Luigi; Svensson, Åke (Contact dermatitis, 2019)
Background A fragrance mix consisting of eight separate fragrance ingredients (fragrance mix I [FM I]) is present in most baseline patch test series. Patch testing with the TRUE Test technique is considered to detect less contact allergy to FM I than testing with the Finn Chamber technique. Objective To investigate the possible significance of batch and patch test method in establishing contact allergy to FM I. Methods Three thousand one hundred and nineteen individuals representing a sample of the general population were patch tested with two batches of FM I with two patch test techniques at six dermatology clinics in five European countries. The TRUE Test technique and the Finn Chamber technique with pet. preparations were used. McNemar's test was used for statistical calculations. Results The contact allergy prevalences varied between 0.7% and 2.6%. The patch tests with the mixes containing Evernia prunastri (oak moss) with a high content of chloratranol/atranol resulted in substantially more positive reactions than the corresponding tests with the mixes containing oak moss with a low content of chloratranol/atranol. The Finn Chamber technique detected significantly more contact allergic reactions than the TRUE Test technique (P < 0.001). Conclusion The Finn Chamber technique detects more contact allergy to FM I than the TRUE Test technique.
Gesehen am 22.01.2020